In-situ growth of boron nitride for the effect of layer-by-layer assembly modified magnesium hydroxide on flame retardancy, smoke suppression, toxicity and char formation in EVA. (January 2021) - Yao, Meng; Wu, Hongjuan; Liu, Hao; Zhou, Zhaoxi; Wang, Tian; Jiao, Yunhong; Qu, Hongqiang
Highlights: Polyphosphazene and boric acid were deposited on the surface of magnesium hydroxide. The multi-element cooperative strategy can effectively improve the flame retardancy of EVA. The in-situ generation of BN can improve the flame retardant efficiency of the flame retardant. Abstract: This work investigates the application of polyphosphazene (PZN) modified magnesium hydroxide (MH) crosslinked by boric acid (BA) (MH-PZPI-BA) for simultaneous flame retardant, smoke suppression and mechanical properties enhancement of ethylene-vinyl acetate (EVA) nanocomposites. The MH-PZPI-BA was prepared by a PZN nano-coating made from hexachlorocyclotriphosphazene and branched polyethyleneimine (bPEI) was deposited onto the MH followed by BA cross-linking bPEI. Then MH-PZPI-BA was incorporated into EVA, and the properties were examined. Compared with pure EVA, the peak heat release rate and total heat released decreased by 82.7% and 44.2%, respectively. The MH-PZPI-BA has an excellent performance in reducing the smoke, CO, and CO2 production rates. The "tortuous path" effect of the boron nitride of in-situ growth hindered the transfer of volatile products, and led to the formation of a compact and robust char layer in condensed phase during combustion, in the combustion process of EVA/MH-PZPI-BA. The tensile strength and elongation at break are improved by 26.1% and 33.5%, respectively.